Capital-Account Crisis and Credit Contraction: The New Nature of Crisis Requires New Policy Responses - Masaru Yoshitomi; Kenichi Ohno (Asian Development Bank Institute (ADBI), 1999)
The malignancy of the Asian crisis comes from its characteristics as twin financial crises: currency crisis (external) and banking crisis (internal). It is a capitalaccount crisis combined with domestic credit contraction, as distinct from the traditional current-account crisis. The new nature of the crisis calls for policy responses entirely different from the conventional ones. The traditional current-account crisis is caused by the deterioration of domestic macroeconomic performance, such as price inflation, fiscal deficits and low saving rates. For this type of crisis, conventional policies such as tight money, fiscal consolidation, structural reforms, and output- and expenditure-switching exchange rate policy are appropriate. However, economic performance of pre-crisis developing Asia was quite good as measured by conventional macroeconomic variables. The critical question is: what consequences will result if the policy prescriptions for the traditional current-account crisis are adopted against the Asian-type capital-account crisis which hits even economies without serious macroeconomic imbalances. We argue that such policy misapplication is likely to transform the initial twin crises into something far more serious, namely the collapse of real economic activity. This paper attempts, first of all, to identify the nature and mechanism of the capital-account crisis. The capital-account crisis is characterized by a massive international capital inflow greatly surpassing the underlying current-account deficit, as well as by the composition of such an inflow being dominated by short-term, foreign currency denominated loans. The resultant double mismatches in both currency and maturity in the balance sheets of domestic financial institutions are responsible for the subsequent twin financial crises: currency precipitation accompanied by international liquidity crisis on the one hand and domestic banking crisis leading to credit contraction on the other. Second, we show how and why policy prescriptions for the traditional current-account crisis, if applied to the capital-account crisis, will exacerbate the problems already inherent in such a crisis. Mounting non-performing loans and abrupt financial disintermediation play key roles in this process. Third, we present alternative policy responses for resolving the twin financial crises which must be implemented by both the governments of the crisis-hit countries as well as the international financial community.
hdl:11540/4110
Keywords: 330